Navigating diagnostic challenges in Bartonella-induced infective endocarditis: a case report - Meriem Ghozzia; Fares Azaiez; Marwa Trabelsi; Mariem Drissa; Rim Ben Romdhane; Kaouther Bachraoui; Rami Tlili; Youssef Ben Ameur (Journal of Medical Case Reports)
Abstract Background Blood culture-negative infective endocarditis presents a significant clinical and diagnostic challenge owing to its atypical presentation and difficulty in identifying causative pathogens. Bartonella henselae, a rare cause of blood culture-negative infective endocarditis, can further complicate its diagnosis and treatment. Case presentation This case report describes the intricate diagnostic journey and therapeutic challenges encountered in a 65-year-old Tunisian female diagnosed with Bartonella henselae-induced infective endocarditis. The patient presented with symptoms of general weakness, weight loss, arthralgia, and a 2-month history of fever along with hepatic involvement characterized by cholestasis and portal hypertension. Despite initial empirical antibiotic therapy leading to temporary improvement, the patient experienced relapse, prompting further investigation. Positive serological tests for Bartonella henselae guided the initiation of targeted antibiotic therapy with rifampin and doxycycline, which resulted in significant clinical improvement. However, the subsequent acute pulmonary edema revealed severe triple-vessel coronary disease, necessitating aortic valve replacement surgery and coronary artery bypass grafting. The patient recovered well postoperatively, with cultures from the aortic valve confirming Bartonella henselae infection. Conclusions This report underscores the importance of heightened awareness, comprehensive diagnostic imaging, and careful consideration of treatment strategies in patients with atypical infective endocarditis. This highlights the need for the early suspicion and identification of Bartonella henselae in BCNIE cases, particularly in patients with relevant epidemiological exposure.